Report on the Coverage & Quality of Information Regarding Engineers in the National Register of Technical Personnel - Planning Commission (Planning Commission, 1957)
The 1957 report by the Scientific and Technical Manpower Division of the Planning Commission assessed the quality and completeness of information on degree-level engineers in the National Register maintained by CSIR. It found that by 1955, the Register covered less than 40% of engineers, with significant underrepresentation of younger professionals and certain disciplines, notably electrical and civil engineering. Government-employed engineers were better represented than those in teaching or private sectors. While coverage of mechanical and mechanical-electrical engineers improved, overall registration stagnated from 1951 to 1955. The study estimated that approximately 15,000 engineers remained unregistered. Recommendations included updating the Register with enhanced data collection methods, improved questionnaires, and periodic statistical analyses to support effective manpower planning and resource allocation. Strengthening the Register is essential for informed decision-making in national scientific and technical development.
Planning Commission Scientific and Technical Manpower Division
Planning Commission Scientific and Technical Manpower Division
Keywords: National Register; Engineers; Technical Manpower; CSIR; Coverage Gaps; Age Distribution; Employment Sectors; Civil Engineers; Electrical Engineers; Mechanical Engineers; Data Quality; Manpower Planning